The Use of Artificial Intelligence (AI) in Developing Interactive Learning Media for Elementary School Teachers - Yudi Hendrilia; Gingga Prananda; Stavinibelia Stavinibelia; Rossa Ramadhona; Edi Ahyani (The Future of Education Journal, 2026)
The rapid development of Artificial Intelligence (AI) technology has transformed various aspects of education, particularly in the creation of more innovative and interactive learning media. However, the utilization of AI by elementary school teachers in classroom instruction remains relatively limited due to insufficient digital literacy and a lack of training opportunities related to AI-based educational technologies. This community service program aimed to enhance elementary school teachers’ competencies in utilizing Artificial Intelligence for the development of interactive learning media. The program was implemented through a participatory training approach consisting of needs assessment, instructional sessions, demonstrations, hands-on practice, mentoring, and evaluation. The training materials focused on the use of various AI platforms, including ChatGPT, Canva AI, Gamma AI, Leonardo AI, and CapCut AI, for the development of instructional media. These platforms enabled teachers to create diverse educational resources more efficiently and creatively. The results demonstrated that the training significantly improved participants’ understanding and skills in utilizing AI technologies for educational purposes. Teachers were able to develop various forms of learning media, including interactive presentations, educational visual content, and instructional videos. Furthermore, participants expressed strong enthusiasm and positive responses toward the training activities, perceiving AI technology as an effective tool for simplifying and enhancing the media development process. In conclusion, this training program contributed positively to supporting digital transformation in education and strengthening elementary school teachers’ competencies in meeting the demands of 21st-century learning. The findings highlight the importance of continuous professional development programs that integrate emerging technologies into educational practice.